2016
DOI: 10.18869/acadpub.hms.22.4.291
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moderate Intensity Aerobic Exercise on Migraine Headache Indexes and Quality of Life Improvement in Women with Migraine

Abstract: Aims: The beneficial effects of physical activities on migraine indices, i. e. frequency, duration, and intensity of the attacks, have been proved by different studies. Despite the fact, it is required to notice the sport characteristics, such as intensity, duration, repetition, and type of the sport, to investigate the beneficial effects of the physical activities on migraine treatment. The aim of this study was to investigate the effects of the Moderate Intensity Aerobic (MIA) exercises on the migraine indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(57 citation statements)
references
References 0 publications
1
56
0
Order By: Relevance
“…All the studies measured the frequency in days/month except Kroll et al, who measured frequency by weeks, and Disttrich et al, who measured frequency by weeks and months. Three of these studies showed improvements in the exercise group . In Hanssen et al, these improvements were superior in the intense exercise group and in Santiago et al, they were superior in the therapy combined with exercise group.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…All the studies measured the frequency in days/month except Kroll et al, who measured frequency by weeks, and Disttrich et al, who measured frequency by weeks and months. Three of these studies showed improvements in the exercise group . In Hanssen et al, these improvements were superior in the intense exercise group and in Santiago et al, they were superior in the therapy combined with exercise group.…”
Section: Resultsmentioning
confidence: 95%
“…Only two studies performed an intention to treat analysis including even though they obtained a loss to follow‐up greater than 20%. In the rest of the studies, the losses to follow‐up were less than 20% …”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations